Colloidal Synthesis of CH3NH3PbBr3 Nanoplatelets with Polarized Emission through Self‐Organization. Issue 7 (11th January 2017) - Liu, Lige; Huang, Sheng; Pan, Longfei; Shi, Li‐Jie; Zou, Bingsuo; Deng, Luogen; Zhong, Haizheng
Abstract: We report a combined experimental and theoretical study of the synthesis of CH3 NH3 PbBr3 nanoplatelets through self‐organization. Shape transformation from spherical nanodots to square or rectangular nanoplatelets can be achieved by keeping the preformed colloidal nanocrystals at a high concentration (3.5 mg mL −1 ) for 3 days, or combining the synthesis of nanodots with self‐organization. The average thickness of the resulting CH3 NH3 PbBr3 nanoplatelets is similar to the size of the original nanoparticles, and we also noticed several nanoplatelets with circular or square holes, suggesting that the shape transformation experienced a self‐organization process through dipole–dipole interactions along with a realignment of dipolar vectors. Additionally, the CH3 NH3 PbBr3 nanoplatelets exhibit excellent polarized emissions for stretched CH3 NH3 PbBr3 nanoplatelets embedded in a polymer composite film, showing advantageous photoluminescence properties for display backlights. Abstract : The synthesis of CH3 NH3 PbBr3 nanoplatelets through a self‐organization process from preformed spherical nanodots is reported. The shape transformation was supported by the material characterization and theoretical simulation, and the resulting nanoplatelets exhibited polarized photoluminescence properties.